PENGARUH KEPEMIMPINAN, DISIPLIN KERJA DAN LINGKUNGAN KERJA TERHADAP KINERJA GURU MELALUI KEPUASAN KERJA SEBAGAI VARIABEL INTERVENING DI SMP NEGERI 1 DAN 2 MANGARAN KABUPATEN SITUBONDO - Vika Khairina; Riska Ayu Pramesthi; Lusiana Tulhusnah (Fakultas Ekonomi dan Bisnis, 2025)
Human resources (HR) are a crucial element that plays a role in supporting institutions to achieve their goals and carry out their functions. HR is also a determining factor in the success of an organization or company in achieving predetermined targets. The purpose of this study was to analyze and test the influence of Leadership, Work Discipline and Work Environment on Teacher Performance through Job Satisfaction as an Intervening Variable at SMP Negeri 1 and 2 Mangaran. The target population in this study were ASN teachers at SMP Negeri 1 and 2 Mangaran who were respondents totaling 33 people. The sampling technique was simple random sampling. The data analysis and hypothesis testing in the study using Structural Equation Model–Partial Least Square (PLS-SEM). The results of the direct influence hypothesis test using the Smart PLS 3.0 application, show that Leadership does not have a significant positive effect on Job Satisfaction, Leadership does not have a significant positive effect on Performance, Work discipline has a positive but insignificant effect on Job Satisfaction, Work discipline has a positive but insignificant effect on Performance, Work environment has a significant negative effect on Job Satisfaction, Work environment has a positive but insignificant effect on Performance and Job satisfaction has a positive but insignificant effect on Performance. Then, the results of the indirect influence hypothesis test show that the variables Leadership on Performance through Job Satisfaction do not have a significant positive effect, Work discipline on Performance through Job Satisfaction has a positive but insignificant effect, and Work environment on Performance through Job Satisfaction does not have a significant positive effect.